1977
DOI: 10.1149/1.2133524
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses with Electrogenerated Halogens: Part II . Oxidation of Malonate Esters

Abstract: The indirect electrochemical oxidation of malonate esters (I) to ethane-1,1,2,2-tetracarboxylate esters (II) has been investigated in greater detail than previously reported. With acetonitrile or an alcohol as the solvent, ethenetetracarboxylate (III), propane-l,l,2,2,3,3-hexacarboxylate (IV), and ethane-1,1,2-tricarboxylate (V) esters were also formed. If the conversion of (I) was limited to 70%, by-product formation was low and 98% yields of (II) were obtained. In acetonitrile, current efficiency was compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…White demonstrated the first example of this via the electrooxidative cyclization of tetramethylpropane-1,1,3,3tetracarboxylate with sodium iodide as a mediator to form tetramethyl-cyclopropane-1,1,2,2-tetracarboxylate (108.4) in 40% yield. 1088 Cathodic reduction of the O−H proton of ethanol generates H 2 and ethoxide, enabling deprotonation of acidic protons from the substrate to form stabilized carbanion 108.11. This anion traps iodinegenerated via anodic oxidation of iodideto an alkyl iodide (108.12).…”
Section: Deprotection Via Redox Chemistriesmentioning
confidence: 99%
“…White demonstrated the first example of this via the electrooxidative cyclization of tetramethylpropane-1,1,3,3tetracarboxylate with sodium iodide as a mediator to form tetramethyl-cyclopropane-1,1,2,2-tetracarboxylate (108.4) in 40% yield. 1088 Cathodic reduction of the O−H proton of ethanol generates H 2 and ethoxide, enabling deprotonation of acidic protons from the substrate to form stabilized carbanion 108.11. This anion traps iodinegenerated via anodic oxidation of iodideto an alkyl iodide (108.12).…”
Section: Deprotection Via Redox Chemistriesmentioning
confidence: 99%
“…It was reported that electrochemical oxidation of tetramethyl propane‐1,1,3,3‐tetracarboxylate 45 in an undivided cell in methanol with NaI as the mediator gave tetramethyl cyclopropanetetracarboxylate 46 in 40% yield (Scheme ) . This is the first example of an electrosynthesis of cyclopropane derivatives.…”
Section: α‐C–x Bond Formation From In Situ Electrogenerated α‐Halogenmentioning
confidence: 74%
“…13 The cyclization of tetramethyl propane-1,1,3,3-tetracarboxylate (37a) carried out back in the 1970s (Ref. 38) was the first electrosynthesis of cyclopropane derivatives that employed alkali metal halides as the mediators. Tetramethyl cyclopropanetetracarboxylate (38a) was synthesized in an undivided cell in boiling methanol in the presence of NaI as the mediator in a chemical yield of 40% and a current efficiency of 82% (Scheme 24).…”
Section: Iii3 Electrocatalytic Synthesis Of Cyclopropanes Involvingmentioning
confidence: 99%